An evaluation of parents' patronage of private primary schools in Abeokuta, Nigeria (2008)
This paper examines the factors determining parents' patronage of private primary schools using Abeokuta as a case study. Purposive sampling techniques was used to slect 10 of 14 approved private primary schools in abeokuta. Total of 210 respondents were used in the study. This comprises 100 parents (42 males, 58 females), 100 private school teachers and 10 school administrators. It also used three questionnairs-(PPSPQ,PPSTQ,PPSAQ) AND A CHECKLIST- (SFC). Data analysis involved the use of percentages, frequencies and t-test. The paper found that private schools are highly patronized in spite of high fees charged. The results indicate that parents' patronage are influenced by: teachers' dedication to work, high level of discipline among the teachers and pupils, early opportunity to train a child, good physical facilities, teaching and use of appropriate medium of instruction for which reasons high fees did not deter parents from patronizing them.